Drosophila virilis histone gene clusters lacking H1 coding segments. - Domier, L.L.; Rivard, J.J.; Sabatini, L.M.; Blumenfeld, M. (Journal of Molecular Evolution, 1986)
Approximately 30-40% of Drosophila virilis DNA complementary to cloned Drosophila histone genes is reduced to 3.4-kilobase-pair (kbp) segments by Bgl I or Bgl II digestion. The core histone genes of a 3.4-kbp Bgl II segment cloned in the plasmid pDv3/3.4 have the same order as the D. melanogaster core histone genes in the plasmid cDm500: H2B H3 H4 H2A. Nonetheless, pDv3/3.4 and cDm500 have different histone gene configurations: In pDv3/3.4, the region between the H2B and H3 genes contains 0.35 kbp and cannot encode histone H1; in cDm500, the region contains 2.0 kbp and encodes histone H1. The lack of an H1 gene between the H2B and H3 genes in 30-40% of D. virilis histone gene clusters suggests that changes in histone gene arrays have occurred during the evolution of Drosophila. The ancestors of modern Drosophila may have possessed multiple varieties of histone gene clusters, which were subsequently lost differentially in the virilis and melanogaster lineages. Alternatively, they may have possessed a single variety, which was rearranged during evolution. The H1 genes of D. virilis and D. melanogaster did not cross-hybridize in vitro under conditions that maintain stable duplexes between DNAs that are 75% homologous. Consequently, D. virilis H1 genes could not be visualized by hybridization to an H1-specific probe and thus remain unidentified. Our observations suggest that the coding segments in the H1 genes of D. virilis and D. melanogaster are greater than 25% divergent.(ABSTRACT TRUNCATED AT 250 WORDS)